Answer:
(a) 3 - 2x - 2x² (b) -21
Step-by-step explanation:
given, y +2x² = 3 -2x
make y the subject:
y = 3 - 2x - 2x²
if y = f(x)
then
f(x) = 3 - 2x - 2x²
(b)<u> to find f(3) we need to replace x with 3:</u>
<u />
3 - 2(3) - 2*(3)²
-21
Answer:
15-7=8
Step-by-step explanation:
you will have to use inverse operation
Answer:
A
Step-by-step explanation:
A cube has 6 sides
Only one side of the cube has 2 on it
The probability of getting 2 would be 1/6
Only one side of the cube has 6 on it
The probability of getting 6 would be 1/6
For both events to happen together
1/6 x 1/6 = 1/36
Answer:
+10
Step-by-step explanation:
Answer:
a) 7y - 3
Step-by-step explanation:
![- 3( - 5y + 2) - (8y - 3)](https://tex.z-dn.net/?f=%20-%203%28%20-%205y%20%2B%202%29%20-%20%288y%20-%203%29)
![15y - 6 - (8y - 3)](https://tex.z-dn.net/?f=15y%20-%206%20-%20%288y%20-%203%29)
![15y - 6 - 8y + 3](https://tex.z-dn.net/?f=15y%20-%206%20-%208y%20%20%2B%203)
![7y - 6 + 3](https://tex.z-dn.net/?f=7y%20-%206%20%2B%203)
![\boxed{\green{ = 7y - 3}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cgreen%7B%20%3D%207y%20-%203%7D%7D)